Results of postoperative radiotherapy of pituitary adenomas - Kulińska, Grażyna; Roszkowski, Krzysztof; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 1999)
The retrospective analysis has been carried out on the group consisted of 58 patients with the pituitary adenoma that were treated with megavolt radiotherapy in Regional Center Oncology in Bydgoszcz between VI 1985 and XII 1994. Patients received 40-60 Gy in reference point and fraction size ranged from 180 to 200 cGy with 3-field technique. The radiotherapy treatment has allowed to reach an improvement of visual area at about 80 percent of patients who has dominant symptomps of local pituitary adenoma’s growth. A local observation which has been done during 5 years (and has been approved by TK examinations) has not show any progress of tumour. After application a total dose higher than 45 Gy a rate of permanent recovery has essentially increased. An increase of treatment area above 36 cm 2 has not cause an improvement of recoveries.A clinical improvement has taken place in every patient who has an acromegalia, prolactinemia and Cushing’s deasease symptoms. About 90 per cent of patient’s who had beem treated by radiotherapy were heeded an aplication of thyroxin, glycocorticoid and sexual hormons. There were no cases of brain necrosis or radiation damage to the optic pathways.